Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18189664
|View full text |Cite
|
Sign up to set email alerts
|

Association between Physical Activity and Sleep Difficulties among Adolescents in Germany: The Role of Socioeconomic Status

Abstract: We examined sleep difficulties among adolescents in Germany and the association with physical activity (PA). Furthermore, we analyzed whether the association varied with the socioeconomic status (SES) among adolescent girls and boys in Germany. Using data from the German Health Interview Examination Survey for Children and Adolescents (KiGGS) study (Wave 2), 6599 adolescents aged 11 to 17 years were included in the analyses. We conducted sex-stratified logistic regression analyses. Dependent variables were unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
(141 reference statements)
2
6
0
Order By: Relevance
“…In fact, our data corroborated with others several studies and con rmed that more than half of teenagers did not sleep well and may showed several consequences of non-good sleep conditions. Independently of the discrepancy of numbers caused by the different methods used to measure sleep conditions several studies corroborating with our data and showed a higher number of teenagers who did not sleep well and did not show sleep quality (10)(11)(12).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In fact, our data corroborated with others several studies and con rmed that more than half of teenagers did not sleep well and may showed several consequences of non-good sleep conditions. Independently of the discrepancy of numbers caused by the different methods used to measure sleep conditions several studies corroborating with our data and showed a higher number of teenagers who did not sleep well and did not show sleep quality (10)(11)(12).…”
Section: Discussionsupporting
confidence: 90%
“…Despite of the most common relationship of different electronic devices with sleep time our data additionally suggest that cellphones are the ones that were also associated with sleep quality (11,12,27) followed by play video games in boys and higher time spent in WhatsApp in girls. In our study sleep quality variables considering questions about sleeping problems, necessity of naps during the day, waking up during sleep at night, di culty to return to sleep when waking up during sleep time and to snore.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations